2015
DOI: 10.1016/j.ijpharm.2015.08.049
|View full text |Cite
|
Sign up to set email alerts
|

A novel scalable manufacturing process for the production of hydrogel-forming microneedle arrays

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 41 publications
3
58
0
Order By: Relevance
“…The needle cavities were filled after applying positive pressure (3–4 bar) to the formulation for 15 min. MN arrays were left to dry for 48 h at room temperature and were then crosslinked by esterification through heating at 80 °C for 24 h (Donnelly et al, 2012a, Donnelly et al, 2014b, Larrañeta et al, 2015, Lutton et al, 2015b). The MN arrays were stored under ambient until assembled into large patches.…”
Section: Methodsmentioning
confidence: 99%
“…The needle cavities were filled after applying positive pressure (3–4 bar) to the formulation for 15 min. MN arrays were left to dry for 48 h at room temperature and were then crosslinked by esterification through heating at 80 °C for 24 h (Donnelly et al, 2012a, Donnelly et al, 2014b, Larrañeta et al, 2015, Lutton et al, 2015b). The MN arrays were stored under ambient until assembled into large patches.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of MN research has been conducted at laboratory scale in small quantities and the development of alternate fabrication approaches has begun to demonstrate scalability. 140,141 There is an inherent dose loading capacity associated with some MN technologies, whereby there is a limit to the amount of vaccine that can be coated on or incorporated in the MN. 1 The inclusion of adjuvants may reduce the vaccine dose required to elicit an appropriate immune response, 86,142 although their inclusion will also necessitate appropriate validation and production in GMP environments.…”
Section: Translation Into Clinical Usementioning
confidence: 99%
“…Importantly, novel fabrication processes for polymeric needles have been described to improve the scalability, and hence accessibility, of these devices. 27,28 For example, Lutton et al (2015), reported on a novel scalable manufacturing process for hydrogel needles. 28 Using a combination of injection molding and roller casting, the authors were able to fabricate highly reproducible polymeric microneedles at ambient temperatures and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 For example, Lutton et al (2015), reported on a novel scalable manufacturing process for hydrogel needles. 28 Using a combination of injection molding and roller casting, the authors were able to fabricate highly reproducible polymeric microneedles at ambient temperatures and low cost. Arrays possessed similar characteristics to microneedles produced using their previously reported centrifugation method, but avoided the labor intensive process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation